AKTIVITAS PEMBINAAN KELOMPOK BERISIKO TINGGI MELALUI PROGRAM PENANGGULANGAN AIDS DI KABUPATEN KAMPAR - Azwar War (LPPM Universitas Abdurrab, 2022)
This research was conducted at the AIDS Commission of Kab. Kampar. The purpose of this study was to determine the activities of developing high-risk groups through the AIDS prevention program by KPA Kampar Regency. This study uses a qualitative approach using observation and interviews with the AIDS Commission (KPA) of Kampar Regency. This article shows that the coaching activities carried out are 1. HIV and AIDS socialization to high-risk groups both medically and religiously, 2. Blood tests for high-risk groups 3. Assistance to HIV-positive risk groups, 4. Realizing behavior change in a better direction, an invitation to no longer commit adultery, strengthen faith in Allah and increase pious deeds. The recommendation from this research is that KPA Kampar Regency further improve the programs that have been implemented.